RESTITUSI DAN KOMPENSASI BAGI KORBAN KEJAHATAN - Kusyandi, Adi (Universitas Wiralodra, 2024)
Restitution and Compensation already exist in Indonesian laws and regulations. This study aims to find out how restitution is carried out for victims and what institutions can act as guarantors for restitution. The method used in this research is library research. Whereas the rights of victims to compensation and restitution in criminal justice are not yet optimal. Community legal knowledge and knowledge of law enforcement officers related to Compensation and Restitution and the absence of legal instruments for victims to defend their rights to Compensation and Restitution are weaknesses in obtaining victims' rights related to Compensation and Restitution.